2020
DOI: 10.1016/j.jvolgeores.2020.107038
|View full text |Cite
|
Sign up to set email alerts
|

Imaging strain localisation in porous andesite using digital volume correlation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 131 publications
2
28
0
Order By: Relevance
“…These authors found that the shear band increased in width as a function of increasing strain and that permeability increased by up to three orders of magnitude at inelastic axial strains of about 0.11 (Farquharson et al 2016). Increases in permeability following shear fracture formation were also reported for andesite from Volcán de Colima deformed at an effective pressure of 10 MPa (Heap et al 2020a).…”
Section: Triaxial Deformation Experimentsmentioning
confidence: 80%
See 4 more Smart Citations
“…These authors found that the shear band increased in width as a function of increasing strain and that permeability increased by up to three orders of magnitude at inelastic axial strains of about 0.11 (Farquharson et al 2016). Increases in permeability following shear fracture formation were also reported for andesite from Volcán de Colima deformed at an effective pressure of 10 MPa (Heap et al 2020a).…”
Section: Triaxial Deformation Experimentsmentioning
confidence: 80%
“…pore-and crack-filling alteration) can increase strength (e.g. Heap et al 2020a). For example, at a given porosity, the argillic alteration that characterises Pinnacle Ridge at Mt Ruapehu (New Zealand) appears to decrease the strength of andesite (Fig.…”
Section: Factors That Influence the Uniaxial Compressive Strength Of Volcanic Rocksmentioning
confidence: 99%
See 3 more Smart Citations